AI as Spiritual Teacher: Reinterpreting Religious Authority through Connolly's Phenomenological-Hermeneutic Lens - Tukma Triputri Daulay; Dody S. Truna; Raden Roro Sri Rejeki Waluyajati (UIN Sunan Gunung Djati Bandung, 2026)
The development of artificial intelligence (AI) has given rise to new dynamics in religious practices and discourse: from interpretation chatbots, automated fatwa applications, to robotics-based representations of religious figures. This article proposes a conceptual reading of this phenomenon using a phenomenological-hermeneutic lens as recommended by Peter Connolly. This research aims to conceptually examine how AI transforms religious experience and authority, and how phenomenological and hermeneutic approaches can be used to understand technologically mediated religious experiences. Rather than assessing the authority of AI normatively or reducing it to a mere social product, this study positions technologically mediated religious experiences as meaningful objects, which also need to be understood from within (phenomenology) and interpreted as new symbolic texts (hermeneutics). The analysis is conducted through a critical reading of interdisciplinary literature on religion, media, and artificial intelligence, with reference to Peter Connolly's phenomenological-hermeneutic ideas on religious experience and the process of symbolic meaning. The results of this study indicate that AI has the potential to function as a new hermeneutic space, not as an absolute substitute for spiritual teachers, but as a relational arena where authority, meaning, and transcendental experience are renegotiated. In this space, the presence of technology expands the horizons of human religious experience, while simultaneously demanding a rereading of legitimacy, awareness, and moral responsibility in digital religious practices. This article concludes with epistemological implications for contemporary religious studies and ethical considerations regarding the limits of digital authority. The study's primary contribution is the development of a theoretical framework for a reflective reading of digital spirituality, one that maintains a balance between the depth of religious experience and a critique of technological commodification.